Arctic Corridors and Northern Voices: Governing marine transportation in the Canadian Arctic (Arviat, Nunavut community report) - Carter, Natalie Ann; Dawson, Jackie; Joyce, Jenna; Ogilvie, Annika (Université d'Ottawa | University of Ottawa, 2017)
Arctic ship traffic has increased by more than 75% since 2005. Most of that increase happened in Nunavut waters. Corridors have been mapped in the Arctic Ocean as part of the Low Impact Shipping Corridors Initiative co-led by Transport Canada, the Canadian Coast Guard, and Canadian Hydrographic Service. Low impact shipping corridors are the current framework for governing shipping in the Canadian Arctic. The intent of the low impact shipping corridors is to reduce the likelihood of marine incidents by providing predictable levels of service to mariners transiting the corridors. Identification of Inuit and northerners’ perspectives on the potential impacts of marine vessels on marine areas used for cultural and livelihood activities, and on community members, and the inclusion of Inuit and northerners’ voices in the development of potential management strategies for the low impact shipping corridors and Arctic marine transportation are key considerations in the current prioritization of the corridors. This report reflects opinions gathered through participatory mapping, focus group discussions, and interviews with Arviat community members who were identified by local organizations as key knowledge holders. Analyses were aimed at understanding Inuit and northerners’ perspectives on the potential impacts of marine transportation on local marine use areas and community members, and on identification of potential management strategies for the low impact shipping corridors and for Arctic vessels management. This report was validated by the research participants.
Keywords: Low impact shipping corridors; Inuit perspectives; Marine transportation governance; Culturally significant marine areas; Arctic shipping impacts